1995
DOI: 10.1115/1.2826984
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Diffraction Forces on an Array of Vertical Cylinders in Bichromatic Bidirectional Waves

Abstract: A complete second-order solution is presented for the hydrodynamic forces due to the action of bichromatic, bidirectional waves on an array of bottom-mounted, surface-piercing cylinders of arbitrary cross section in water of uniform finite depth. Based on the constant structural cross section, the first-order problem is solved utilizing a two-dimensional Green function approach, while an assisting radiation potential approach is used to obtain the hydrodynamic loads due to the second-order potential. Results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…From Fig. 3, it is found that the present results are in good 347 agreement with those of the study by Vazquez (1995). In addition, even though the 348 mesh in the first case is much coarser than that in the second case, the two test cases 349 provide almost the same results, which indicates that convergence is achieved.…”
supporting
confidence: 77%
“…From Fig. 3, it is found that the present results are in good 347 agreement with those of the study by Vazquez (1995). In addition, even though the 348 mesh in the first case is much coarser than that in the second case, the two test cases 349 provide almost the same results, which indicates that convergence is achieved.…”
supporting
confidence: 77%